The conflict between illusion and reality in Edward Albee's plays - Baužytė, Galina (Literatūra, 1973)
The dramas of E. Albee reflect many typical traits of the modern Western theatre, such as the tendency towards conventionality, the return to myth, parable, the ancient ritual drama and medieval mystery. Albee analyses such essential problems of the 20th century drama as the problem of illusion and reality, that of free choice and determinism and also the problem of the relationship between artistic imagination and reality. The author of the article focuses her attention on the analysis of the conflict between illusion and reality in the dramas "Who's Afraid of Virginia Woolf?" and "Tiny Alice". The triumph of truth over the illusion created by the heroes (the myth of a son) acquires a tragic meaning in the first play. The heroes are crushed by the merciless truth and are facing it with anguish. The playwright asserts the truth whatever it is and opposes it to illusionary optimism. In the drama "Tiny Alice" Julian's religious illusions are the main cause of his sufferings and, finally, of his death. Albee opposes his views to those of Eugene O'Neill who has asserted the necessity of life-illusions in the drama "The Iceman Cometh". The dramatic form of "Tiny Alice" shows Albee's relations with the tradition of Strindberg's dream-plays and Eliot's ritual drama. The musical-rhythmical structure of Albee's plays is made a special subject of analysis in the article. Exposing the void standards of the American society Albee employs the technique of the theatre of the absurd. However, he rejects the hopeless pessimism of the absurdists and asserts the necessity to face life without illusions.
Keywords: -